FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KELUHAN COMPUTER VISION SYNDROME (CVS) PADA OPERATOR KOMPUTER PT. BANK KALBAR KANTOR PUSAT TAHUN 2012 - ., Yeni Anggraini (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Computer usage leads to various health problem including eyediscomfort. The complex of eye and vision problems related to prolonged useof Visual Display Terminal (VDT) has been termed as Computer VisionSyndrome (CVS). Factors related to CVS are age, sex, work period in years,eye disorder, work duration in hours, rest breaks frequency, condition oflighting and temperature in work environment.Objective: This research aimed to identify the relationship between the VDTworkers factor, VDT usage and work environment with CVS complaints oncomputer operators at Center Office of Bank Kalbar in 2012.Methodology: This research was an analytic observational study with crosssectional approach. Sampels were choosen by total sampling method.Seventy eight computer operators that fulfilled the researchs criteriasincluded as a subject. The data were collected from questionnaire answersand observation of work environment, then analyzed by using Fishers ExactTest.Result: This research found that 88,5% respondents had CVS complaints.Based on statistical result, the age, VDT usage and work environment factorsdidnt have any significant relationship with CVS complaints (p > 0,05). Sex,work period in years and eye disorder showed significant relationship withCVS complaints (p < 0,05).Conclusion : There are relationship between VDT workers factor with CVScomplaints in computer operators at Center Office of Bank Kalbar in 2012.Keywords: computer vision syndrome, VDT worker, VDT usage, workenvironment1. Medical School, Faculty of Medicine, Tanjungpura University, Pontianak,West Kalimantan.email:anggrainYee@yahoo.co.id.2. Department of Public Health, Medical School, Faculty of Medicine,Tanjungpura University, Pontianak, West Kalimantan.3. Department of Pharmacology, Medical School, Faculty of Medicine,Tanjungpura University, Pontianak, West Kalimantan.